Investigating the Effect of Substrate Materials on Wearable Immunoassay Performance - Lee, Khai T (Langmuir : the ACS journal of surfaces and colloids, 2017)
Immunoassays are ubiquitous across research and clinical laboratories, yet little attention is paid to the effect of the substrate material on the assay performance characteristics. Given the emerging interest in wearable immunoassay formats, investigations into substrate materials that provide an optimal mix of mechanical and bioanalytical properties are paramount. In the course of our research in developing wearable immunoassays which can penetrate skin to selectively capture disease antigens from the underlying blood vessels, we recently identified significant differences in immunoassay performance between gold and polycarbonate surfaces, even with a consistent surface modification procedure. We observed significant differences in PEG density, antibody immobilization, and nonspecific adsorption between the two substrates. Despite a higher PEG density formed on gold-coated surfaces than on amine-functionalized polycarbonate, the latter revealed a higher immobilized capture antibody density and lower nonspecific adsorption, leading to improved signal-to-noise ratios and assay sensitivities. The major conclusion from this study is that in designing wearable bioassays or biosensors, the design and its effect on the antifouling polymer layer can significantly affect the assay performance in terms of analytical specificity and sensitivity